The relationship between market information and entrepreneurial orientation: the case of smallholder honey producers in Northern Uganda - Amuko, Walter; Kalule, Stephen W.; Odongo, Walter (Agricultural and Food Economics, 2023)
The purpose of this study was to determine the influence of market information on entrepreneurial orientations of smallholder honey producers. Design/methodology/approach: A cross-sectional study design with sample of 250 honey producers was used. Structural equations modeling was used to analyze the hypothesized relationships. Findings: Results show that product quality, trader preferences and consumer preferences are the main market information needs that influence entrepreneurial orientation of honey producers. Further, the attributes of market information quality, i.e., information credibility, timeliness, accuracy and usability positively influence entrepreneurial orientation. Practical implications: Results of this study calls for prioritization of better access to regular, reliable and usable market information for honey producers in development programs and policies so as to enhance farmer entrepreneurial orientations and product development. Social implications: Smallholder honey producers are more likely to efficiently deliver innovative products if development interventions across the public and non-public sector divide become responsive to their marketing information needs as well the quality of market information provided. Originality/value: The study uses original data from honey producers to demonstrate the role that marketing information needs as well as market information quality play in catalyzing smallholder farmer entrepreneurial orientation.
Keywords: Information quality; Information needs; Smallholder farmers; Honey production; Entrepreneurial orientation; Market information